Ensino de instrumento musical para pessoas com deficiência: um estudo na Escola Especial de Música Juarez Johnson - Ferreira, Mayara de Brito (2019)
This work explores the teaching of musical instruments for people with disabilities, their relationships and their teaching processes. The research developed had as general objective to understand how has been characterized the teaching of music in the classes of musical instrument in the Special School of Music Juarez Johnson (EEMJJ). And from this focus, the work has the specific objectives to identify and understand: a) the main proposals and practices of music teaching in the school; b) the practices of instrument teaching; c) the main conceptions of the teachers about the instrument classes. The research was methodologically based around a case study, involving the practices and conceptions of three musical instrument teachers, around their classes developed with seven students of musical instrument of the EEMJJ, in the city of João Pessoa-PB. The selected students have the following disabilities and special needs: two students with Down Syndrome, one with hearing impairment, one with autism, two students with intellectual disability, one student with Sturge-Weber Syndrome. The theoretical basis proposed for this research is based on texts about music teaching and Special Education. Thus, works of the area of Musical Education, Special Musical Education, Pedagogy of the Musical Instrument were used; and texts from some areas that relate to the topic addressed as Special Education, Education, and Sociology, to cover and deepen the discussion. The research covers topics such as: people with disabilities, society and history; musical education and inclusion; diversity in music teaching; musical instrument teaching and inclusive education. The methodological procedures had as instruments of data collection: bibliographic research; indirect observation of the classes (through video, without the presence of the researcher) and video recording; semi-structured interviews and audio recording. The organization and analysis of the data compares the annotations of the observations of the recorded classes and the transcripts of the interviews, listing the highlights of the conceptions and strategies of teaching in relation to the discussions brought in the work. The analyzed data emphasize that within the special musical education there are points to be seen as positive, as well as difficulties. And that it is necessary to discuss in a real way proposals of music teaching for these students, proposals that are coherent with the needs of the students. And that it is worth to re-signify and seek different means of teaching for a meaningful musical education for students with disabilities.